Combustion, Physical, and Mechanical Characterization of Composites Fuel Briquettes from Carbonized Banana Stalk and Corncob - Segun Emmanuel Ibitoye; Rasheedat Modupe Mahamood; Tien-Chien Jen; Esther Titilayo Akinlabi (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
The United States Environmental Protection Agency (EPA) has reported that consumption of fossil fuels and their products has contributed about 65% of the global greenhouse gas emission. Therefore, it is expedient to look for alternative energy sources for an eco-friendly environment. The EPA recommended using biomass energy as a promising stabilization option to alleviate global climate change. This study focused on developing composites fuel briquettes from a blend of carbonized corncob and banana stalk. Carbonization was carried out at 380 oC, while 60 min was adopted as the residence time. Briquettes were manufactured at different blending ratios (90CC:10BS, 80CC:20BS, 70CC:30BS, 60CC:40BS and 50CC:50BS of corncob: banana stalk, respectively) and compaction pressures (50, 70 and 90 kPa) using gelatinized starch as binder. The manufactured briquettes' calculated and actual calorific values varied between 18.98-22.07 MJ/kg and 20.22-23.12 MJ/kg, respectively, while shatter indices were in the range of 38.22-89.34%. The compressed and relaxed densities of the fuel briquettes were in the range of 0.32-1.39 g/cm3 and 0.22-1.02 g/cm3, respectively. The relaxation ratio and water resistance properties varied between 1.11- 2.21 and 11-23 min, respectively. Analyses of the results revealed that compaction pressure, blending ratio, and particle size substantially affect the combustion and physico-mechanical characteristics of the manufactured fuel briquettes. When optimum combustion and physico-mechanical properties are required, a sample made from 90CC:10BS (S1) is recommended for use. The fuel briquettes manufactured in this study possess the required thermal and physico-mechanical properties of solid fuel; therefore, it is recommended for different applications.